2012
DOI: 10.1002/elps.201100434
|View full text |Cite
|
Sign up to set email alerts
|

A neurosteroid analogue photolabeling reagent labels the colchicine‐binding site on tubulin: A mass spectrometric analysis

Abstract: Previous studies have shown that the neurosteroid analogue, 6-Azi-pregnanolone (6-AziP), photolabels voltage-dependent anion channels and proteins of approximately 55 kDa in rat brain membranes. The present study used two dimensional electrophoresis and nano-electrospray ionization ion trap mass spectrometry (nano-ESI-MS) to identify the 55 kDa proteins (pI 4.8) as isoforms of β-tubulin. This identification was confirmed by immuno-blot and immunoprecipitation of photolabeled protein with anti-β-tubulin antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…It is also possible that 6-AziP undergoes fragmentation during electrospray ionization, which would result in an adduct weight for 6-AziP different from that with simple loss of two nitrogens (Brunner, 1993) and would confound the search protocols. Previous studies with 6-AziP-labeled proteins and synthetic peptides detected peptides containing an intact 6-AziP moiety and failed to detect fragmented 6-AziP adducts (Chen et al, 2012a). Therefore, it is unlikely that we failed to detect photolabeled peptides because of systematic 6-AziP fragmentation during electrospray ionization.…”
Section: Identification Of Neurosteroid Photoincorporationmentioning
confidence: 73%
See 1 more Smart Citation
“…It is also possible that 6-AziP undergoes fragmentation during electrospray ionization, which would result in an adduct weight for 6-AziP different from that with simple loss of two nitrogens (Brunner, 1993) and would confound the search protocols. Previous studies with 6-AziP-labeled proteins and synthetic peptides detected peptides containing an intact 6-AziP moiety and failed to detect fragmented 6-AziP adducts (Chen et al, 2012a). Therefore, it is unlikely that we failed to detect photolabeled peptides because of systematic 6-AziP fragmentation during electrospray ionization.…”
Section: Identification Of Neurosteroid Photoincorporationmentioning
confidence: 73%
“…6-azipregnanolone (6-AziP) is a neurosteroid-analog photolabeling reagent that was shown previously to label VDAC and ␤-tubulin covalently (Darbandi-Tonkabon et al, 2003, 2004Chen et al, 2012a). Studies that used tritiated 6-AziP to label rat brain membranes and separated the photolabeled proteins with native gel electrophoresis showed that 6-AziP also labeled native GABA A receptors (data not shown).…”
Section: Introductionmentioning
confidence: 93%
“…However, it is also recognized that none of these molecular targets have satisfied the criteria of being both necessary and sufficient to produce the complete anesthetic state. Other plausible targets have included mitochondria, tubulin, and the synaptic vesicle transport and release machinery (17,(55)(56)(57)(58). For example, SNAP-25 and syntaxin specifically bind propofol (7).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 This fact has prompted us to examine the series of other biologically active colchicine derivatives, i.e.…”
Section: Maldi Mass Spectramentioning
confidence: 99%